Youth Olympic Games: from vision to success - Miang, N. S. (The Sport Journal, 2011)
IOC vice president and Singapore Youth Olympic Games Organizing Committee chairman about the Youth Olympic Games. Introduction Good afternoon, ladies and gentlemen. When Pierre de Coubertin revived the Olympic Games in 1894, he sought to do more than just create a modern sporting competition. He founded the Olympic Movement as an education movement, believing that sport would contribute to the harmonious and well-balanced development of the body, mind and character, and helped create a more peaceful and better world. It is the convergence of sport, culture and education that defines the concept of Olympism and the modern Olympic Movement. It is therefore my pleasure and privilege to share with you the Youth Olympic Games, a new creation that truly epitomize the spirit of the modern Olympic Movement.